Former Yugoslav Republic of Macedonia : Third Review Under the Stand; By Arrangement and Request for Rephasing of Access; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
Macedonia's economic performance under the program has remained strong, reflecting the authorities' commitment to build on the progress made and to advance the reform agenda. The average inflation rate was 2.3 percent, although it started to pick up recently owing to a relatively high increase in food prices, reflecting the global trend. On the expenditure side, the authorities will improve the quality of spending and redirect public spending to more productive uses, such as health, education, and infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet